Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 215400 by ajfour last updated on 05/Jan/25

Commented by ajfour last updated on 05/Jan/25

Correction I think-  Find b, given a.

$${Correction}\:{I}\:{think}-\:\:{Find}\:{b},\:{given}\:{a}. \\ $$

Answered by mr W last updated on 06/Jan/25

Commented by mr W last updated on 06/Jan/25

r=1  α=(a/r), β=(b/r), γ=(c/γ)  d=b−r+c−r=b+c−2r  d^2 =b^2 +c^2 =b^2 +c^2 +4r^2 +2bc−4r(b+c)  2r^2 +bc−2r(b+c)=0  2+βγ−2(β+γ)=0  ⇒γ=((2(β−1))/(β−2))  x=a−(√(c^2 −b^2 ))  y=b−(√(a^2 −d^2 ))=b−(√(a^2 −b^2 −c^2 ))  [a−(√(c^2 −b^2 ))]^2 +[b−(√(a^2 −b^2 −c^2 ))]^2 =b^2   a^2 −b^2 =a(√(c^2 −b^2 ))+b(√(a^2 −b^2 −c^2 ))  α(√(γ^2 −β^2 ))+β(√(α^2 −β^2 −γ^2 ))=α^2 −β^2   ⇒α(√(4(((β−1)/(β−2)))^2 −β^2 ))+β(√(α^2 −β^2 −4(((β−1)/(β−2)))^2 ))=α^2 −β^2

$${r}=\mathrm{1} \\ $$$$\alpha=\frac{{a}}{{r}},\:\beta=\frac{{b}}{{r}},\:\gamma=\frac{{c}}{\gamma} \\ $$$${d}={b}−{r}+{c}−{r}={b}+{c}−\mathrm{2}{r} \\ $$$${d}^{\mathrm{2}} ={b}^{\mathrm{2}} +{c}^{\mathrm{2}} ={b}^{\mathrm{2}} +{c}^{\mathrm{2}} +\mathrm{4}{r}^{\mathrm{2}} +\mathrm{2}{bc}−\mathrm{4}{r}\left({b}+{c}\right) \\ $$$$\mathrm{2}{r}^{\mathrm{2}} +{bc}−\mathrm{2}{r}\left({b}+{c}\right)=\mathrm{0} \\ $$$$\mathrm{2}+\beta\gamma−\mathrm{2}\left(\beta+\gamma\right)=\mathrm{0} \\ $$$$\Rightarrow\gamma=\frac{\mathrm{2}\left(\beta−\mathrm{1}\right)}{\beta−\mathrm{2}} \\ $$$${x}={a}−\sqrt{{c}^{\mathrm{2}} −{b}^{\mathrm{2}} } \\ $$$${y}={b}−\sqrt{{a}^{\mathrm{2}} −{d}^{\mathrm{2}} }={b}−\sqrt{{a}^{\mathrm{2}} −{b}^{\mathrm{2}} −{c}^{\mathrm{2}} } \\ $$$$\left[{a}−\sqrt{{c}^{\mathrm{2}} −{b}^{\mathrm{2}} }\right]^{\mathrm{2}} +\left[{b}−\sqrt{{a}^{\mathrm{2}} −{b}^{\mathrm{2}} −{c}^{\mathrm{2}} }\right]^{\mathrm{2}} ={b}^{\mathrm{2}} \\ $$$${a}^{\mathrm{2}} −{b}^{\mathrm{2}} ={a}\sqrt{{c}^{\mathrm{2}} −{b}^{\mathrm{2}} }+{b}\sqrt{{a}^{\mathrm{2}} −{b}^{\mathrm{2}} −{c}^{\mathrm{2}} } \\ $$$$\alpha\sqrt{\gamma^{\mathrm{2}} −\beta^{\mathrm{2}} }+\beta\sqrt{\alpha^{\mathrm{2}} −\beta^{\mathrm{2}} −\gamma^{\mathrm{2}} }=\alpha^{\mathrm{2}} −\beta^{\mathrm{2}} \\ $$$$\Rightarrow\alpha\sqrt{\mathrm{4}\left(\frac{\beta−\mathrm{1}}{\beta−\mathrm{2}}\right)^{\mathrm{2}} −\beta^{\mathrm{2}} }+\beta\sqrt{\alpha^{\mathrm{2}} −\beta^{\mathrm{2}} −\mathrm{4}\left(\frac{\beta−\mathrm{1}}{\beta−\mathrm{2}}\right)^{\mathrm{2}} }=\alpha^{\mathrm{2}} −\beta^{\mathrm{2}} \\ $$

Commented by ajfour last updated on 06/Jan/25

Yeah this is finer, i could follow  smoothly, Sir.

$${Yeah}\:{this}\:{is}\:{finer},\:{i}\:{could}\:{follow} \\ $$$${smoothly},\:{Sir}. \\ $$

Answered by ajfour last updated on 05/Jan/25

I get underneath relation:  [(√((((b−1)/((b/2)−1)))^2 −b^2 ))−a]^2 +[(√((((b−1)/((b/2)−1))+b−2)^2 −a^2 ))−b]^2 =a^2 +b^2

$${I}\:{get}\:{underneath}\:{relation}: \\ $$$$\left[\sqrt{\left(\frac{{b}−\mathrm{1}}{\frac{{b}}{\mathrm{2}}−\mathrm{1}}\right)^{\mathrm{2}} −{b}^{\mathrm{2}} }−{a}\right]^{\mathrm{2}} +\left[\sqrt{\left(\frac{{b}−\mathrm{1}}{\frac{{b}}{\mathrm{2}}−\mathrm{1}}+{b}−\mathrm{2}\right)^{\mathrm{2}} −{a}^{\mathrm{2}} }−{b}\right]^{\mathrm{2}} ={a}^{\mathrm{2}} +{b}^{\mathrm{2}} \\ $$$$ \\ $$

Answered by mr W last updated on 05/Jan/25

Commented by mr W last updated on 05/Jan/25

r=1  c=(b/(cos θ))  a=b(tan θ+cos θ)  d=(√(b^2 +c^2 ))=b(√(1+(1/(cos^2  θ))))  bc=(b+c+d)r  ⇒b=(1+cos θ+(√(1+cos^2 θ)))r  ⇒a=(tan θ+cos θ)(1+cos θ+(√(1+cos^2  θ)))r  with 0<θ<(π/2)

$${r}=\mathrm{1} \\ $$$${c}=\frac{{b}}{\mathrm{cos}\:\theta} \\ $$$${a}={b}\left(\mathrm{tan}\:\theta+\mathrm{cos}\:\theta\right) \\ $$$${d}=\sqrt{{b}^{\mathrm{2}} +{c}^{\mathrm{2}} }={b}\sqrt{\mathrm{1}+\frac{\mathrm{1}}{\mathrm{cos}^{\mathrm{2}} \:\theta}} \\ $$$${bc}=\left({b}+{c}+{d}\right){r} \\ $$$$\Rightarrow{b}=\left(\mathrm{1}+\mathrm{cos}\:\theta+\sqrt{\mathrm{1}+\mathrm{cos}\:^{\mathrm{2}} \theta}\right){r} \\ $$$$\Rightarrow{a}=\left(\mathrm{tan}\:\theta+\mathrm{cos}\:\theta\right)\left(\mathrm{1}+\mathrm{cos}\:\theta+\sqrt{\mathrm{1}+\mathrm{cos}^{\mathrm{2}} \:\theta}\right){r} \\ $$$${with}\:\mathrm{0}<\theta<\frac{\pi}{\mathrm{2}} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com